Resilience assessment of integrated energy systems under hurricanes - Zhang, Huajun (Nanyang Technological University, 2020)
Our modern society depends deeply on critical infrastructure (CI) systems, such as the energy, transportation and water system, etc., for normal function and development. Among these CIs, energy systems are of fundamental importance as they provide energy for all other systems as well as themselves to maintain normal operation. Power systems and natural gas (NG) systems are two vitally important energy supply systems that are very vulnerable to some relatively rare but extreme weather events (EWEs), such as ice storms and hurricanes. EWEs could cause extensive damage to exposed energy facilities, which may lead to disruptions of energy service, and could further result in enormous impacts on the whole society and economics. Considerable public concern has been raised on the threat of EWEs on energy systems. On the other hand, complex interdependence among CIs is increasing due to the expanded connections among them. Specifically in the energy systems, the power system increasingly relies on the NG system for the primary fuel of gas due to the building of considerably gas-fired generation plants for its promising potentials. At the same time, the NG system is gradually dependent more on the power system to operate, for example, using electricity to drive gas compressors instead of gas as before. With the ever-growing interdependence, it is clear that the conventional standalone system analysis viewpoint becomes insufficient and inadvisable. The CI internal complexity, rising interdependence as well as environmental risks from EWEs could work together to amplify undesirable disruptive effects and threat the reliable and continuous supply of energy. To manage this increased exposure to threats induced by EWEs and risks associated with interdependence, this thesis seeks to integrate the existing knowledge and develop methods to evaluate the impact of gas fuel supply on the reliability of transmission power systems, to assess the power system performance under the spatial-temporal impact of hurricanes, to quantify the resilience of integrated transmission power systems and NG systems under hurricanes, and to measure the frequency resilience of transmission power systems under hurricanes. It includes investigating the impact of gas fuel supply on the power system reliability from a long-term time scale, exploring the hurricane wind and rainfall impact on the power system reliability during the hurricane event, establishing integrated power and NG system resilience analysis models and framework, studying the effect of frequency control process on power system performance under hurricanes, and proposing corresponding assessment methods. Besides, this thesis also develops a multi-attribute construct of indices to quantify the power system and the NG system performance from both the operation and the infrastructure perspective, e.g., load shedding related indices, frequency related indices, and component damage related indices. Based on the assessment indices, integrated proactive suggestions can be provided to guide the preparation of the power system or the integrated energy systems for the approaching hurricane. The methods generated could also be used in the co-planning of power systems and fuel supply systems or serve as a decision-making tool for the selection of resilience enhancement strategies in the future.